Insect Arylalkylamine N-Acyltransferases: Mechanism and Role in Fatty Acid Amide Biosynthesis - O'Flynn, Brian G.; Suarez, Gabriela; Hawley, Aidan J.; Merkler, David J. (Frontiers in Molecular Biosciences, 2018)
Arylalkylamine N-acyltransferases (AANATs) catalyze the formation of an N-acylamide from an acyl-CoA thioester and an amine. One well known example is the production of N-acetylserotonin from acetyl-CoA and serotonin, a reaction in the melatonin biosynthetic pathway from tryptophan. AANATs have been identified from a variety of vertebrates and invertebrates. Considerable efforts have been devoted to the mammalian AANAT because a cell-permeable inhibitor specifically targeted against this enzyme could prove useful to treat diseases related to dysfunction in melatonin production. Insects are an interesting model for the study of AANATs because more than one isoform is typically expressed by a specific insect and the different insect AANATs (iAANATs) serve different roles in the insect cell. In contrast, mammals express only one AANAT. The major role of iAANATs seem to be in the production of N-acetyldopamine, a reaction important in the tanning and sclerotization of the cuticle. Metabolites identified in insects including N-acetylserotonin and long-chain N-fatty acyl derivatives of dopamine, histidine, phenylalanine, serotonin, tyrosine, and tryptophan are likely produced by an iAANAT. In vitro studies of specific iAANATs are consistent with this hypothesis. In this review, we highlight the current metabolomic knowledge of the N-acylated aromatic amino acids and N-acylated derivatives of the aromatic amino acids, the current mechanistic understanding of the iAANATs, and explore the possibility that iAANATs serve as insect “rhymezymes” regulating photoperiodism and other rhythmic processes in insects.